(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
This study examines the "Influence of Government Regulatory Policies on Corporate Governance and Ethical Practices in Cross River State, Nigeria." The main objectives were to assess the effectiveness of government regulatory policies in promoting corporate governance and ethical practices, and to identify the challenges faced by regulatory bodies in enforcing these standards. A mixed-methods approach was employed, combining both quantitative and qualitative data collection techniques. A sample of 180 participants, including regulatory officials, corporate executives, and community members, was surveyed. Data was collected through structured questionnaires, in-depth interviews, and focus group discussions. The study found that the majority of participants perceived government regulations as effective in promoting corporate governance and ethical practices, although challenges in compliance were evident. The findings showed that while most organizations comply with regulatory policies to a moderate extent, there are significant obstacles such as lack of resources, political interference, and inadequate public awareness. Furthermore, regulatory bodies face difficulties in enforcing compliance due to poor enforcement mechanisms and inconsistent policy implementation. The effectiveness of government regulations significantly influences the level of compliance with corporate governance and ethical standards in the region. However, the study emphasizes the need for improved regulatory frameworks, better resource allocation, and stronger enforcement measures. It is recommended that the government strengthen its regulatory capacity, increase public awareness campaigns, and ensure more robust enforcement mechanisms to enhance corporate governance and ethical practices in Cross River State.